2005
DOI: 10.1007/s10661-005-2282-4
|View full text |Cite
|
Sign up to set email alerts
|

An Italian Study on Cryptosporidium and Giardia in Wastewater, Fresh Water and Treated Water

Abstract: Cryptosporidium oocysts and Giardia cysts has been isolated from waters worldwide. In Italy, studies on these parasites in the environment are still limited due to absence of epidemiological evidence and difficulty of adequate methodologies of sampling and analysis. The new Drinking Water Directive 98/83/CE states that Cryptosporidium has to be determined in water intended for human consumption if Clostridium perfringens is detected. This investigation contributes to the knowledge of both Cryptosporidium and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
5
37
1
4
Order By: Relevance
“…But unlike school B, both samples from school E were found positive for the presence of Cryptosporidium oocysts and Giardia cysts .In this case, the source of contamination is more likely to be birds because birds' fecal remaining was observed on the ground that surrounded the swimming pool. This result correlates with the results of another study [7]. This result indicates that shading the swimming pools or having indoor swimming pools might decrease the risk of outdoor contamination with Cryptosporidium oocysts and Giardia cysts.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…But unlike school B, both samples from school E were found positive for the presence of Cryptosporidium oocysts and Giardia cysts .In this case, the source of contamination is more likely to be birds because birds' fecal remaining was observed on the ground that surrounded the swimming pool. This result correlates with the results of another study [7]. This result indicates that shading the swimming pools or having indoor swimming pools might decrease the risk of outdoor contamination with Cryptosporidium oocysts and Giardia cysts.…”
Section: Resultssupporting
confidence: 89%
“…One of the significant observations which could be related to the variability of the results between the different swimming pools is due to the type of the swimming pools. A study in Italy indicated that outdoor swimming pools tend to be more contaminated with Cryptosporidium oocysts and Giardia cysts [7]. In addition to the contamination of the swimming pool caused by humans, this study demonstrated that outdoor swimming pools were more contaminated with Cryptosporidium and Giardia compared to indoor swimming pools.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations